(3cJGH GdSdWGf SdjeGf Hf Sdje GdYKeGfi Edi GdTQja aNQ GdOjf GdeWgQ Hf TQa GdOjf hLhGHgs - (3GdSdWGf SdjeGf Hf Sdje GdYKeGfjs
(3ChdgG (B:s
(3gPG CeKGdfG GdTQja GdSGeI, hNWGHfG GdUeOGfi CQSdfGg Zdi hChd GdLhGH (B: (3fhQ Gddg TehS GdESdGe hGWdYgG s
(3BNQgG (B:s
(3hBNQ GdLhGH (B: (3hjJMed ef WGYJce eG jTb Ydi ZjQg hTQN HEYeGdg ef GdCeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3hGdKGfi SfI (B962(3g`s
(3cJHJ HQSe LeGd GdESdGe eLdi Hf fGUQ GdCHjV (B[ (3UhQI GdcJGHs
(3hLhGHg UOQ GdChd HGdbSWfWjfjI SfI (B956(3g` s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs